Plant Functional Traits, but Not Community Composition, Are Affected by Summer Precipitation and Herbivory in an Old‐Field Ecosystem - Julia N. Eckberg; Mariano A. Rodríguez‐Cabal; M. Noelia Barrios‐García; Nathan J. Sanders (Ecology and Evolution)
ABSTRACT Both precipitation and herbivores can independently control plant community composition and ecosystem function. However, few studies have experimentally examined the potential interactive effects of altered precipitation and herbivores on plant communities and plant traits. Here, we manipulated summer precipitation and insect presence in an old‐field ecosystem and quantified their interactive effects on plant community structure and functional traits. Overall, the effect of an insect herbivore on the plant community was contingent on the precipitation treatment. There were no experimental effects on total plant biomass or plant species richness, but grass biomass was higher in the absence of insect herbivores only in reduced summer precipitation plots. Furthermore, plant functional diversity and the community‐averaged trends of several plant functional traits related to resource use and herbivore resistance varied systematically with reduced precipitation and insect presence. We demonstrate that the effect of reduced precipitation on plant biomass, functional diversity, and the community‐averaged trends of plant functional traits can be mediated by the presence of insects. Our findings further suggest that the functional traits of the common plant species in the community are the most affected by the combined manipulation of altered summer precipitation and insect presence.